2016
DOI: 10.1080/0284186x.2016.1191665
|View full text |Cite
|
Sign up to set email alerts
|

Proton pencil beam scanning for mediastinal lymphoma: treatment planning and robustness assessment

Abstract: Background: Modern radiotherapy (RT) for lymphoma is highly personalized. While advanced imaging is largely employed to define limited treatment volumes, the use of proton pencil beam scanning (PBS) for highly conformal lymphoma RT is still in its infancy. Here, we assess the dosimetric benefits and feasibility of PBS for mediastinal lymphoma (ML). Materials and methods: Ten patients were planned using PBS for involved-site RT. The initial plans were calculated on the average four-dimensional computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Several dosimetric studies comparing proton with photon plans [8][9][10][11][12][13][14][15][16][17][18][19][20][21] have been conducted in an effort to establish the benefit and indications for the use of proton therapy in lymphoma, with the vast majority focusing on mediastinal involvement. They showed that there is an individualized and potential benefit in patients with dose reduction to the heart, lungs, and breasts with proton therapy compared with 3D conformal radiotherapy or IMRT.…”
Section: Different Techniques In Delivering Proton Therapymentioning
confidence: 99%
“…Several dosimetric studies comparing proton with photon plans [8][9][10][11][12][13][14][15][16][17][18][19][20][21] have been conducted in an effort to establish the benefit and indications for the use of proton therapy in lymphoma, with the vast majority focusing on mediastinal involvement. They showed that there is an individualized and potential benefit in patients with dose reduction to the heart, lungs, and breasts with proton therapy compared with 3D conformal radiotherapy or IMRT.…”
Section: Different Techniques In Delivering Proton Therapymentioning
confidence: 99%
“…For treatments delivered by proton pencil beam, the interplay between the scanning beam and a moving target creates dose inhomogeneities within the target, degrading the dose distribution. Larger spots and dose repainting are used to maintain robustness of mediastinal lymphoma proton pencil-beam treatments (61). With the small cohorts in dosimetric studies comparing photon and proton lymphoma plans, it is difficult to discern if all plans are of deliverable quality, especially because some use the approach of simple geometric expansions as motion management without motion evaluation.…”
Section: Review Of Dosimetric Studies and Specific Oarsmentioning
confidence: 99%
“…Of the 9 published studies evaluating the dosimetric benefits of proton therapy on cardiac dose, 7 demonstrated improvements compared with photon techniques (53,(55)(56)(57)(58)(59)(61)(62)(63) (Table E1; available online at www.redjournal.org). Seven of these studies evaluated passive-scanning proton therapy, and 2 evaluated an active scanning technique.…”
Section: Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment of mediastinal lymphoma, there has been increased interest over the last 5 years in utilizing proton therapy techniques as well as breath-hold techniques with 3dimensional conformal radiation therapy (RT) or intensity-modulated RT in an effort to reduce the radiation dose to the organs at risk [1][2][3][4][5][6]. Combining both breath-hold techniques and proton therapy has been less common owing to concerns about the reproducibility of breath hold, the impact of poor reproducibility when using proton therapy, and the lack of volumetric image-guided RT and real-time diaphragm monitoring of the breath hold.…”
Section: Introductionmentioning
confidence: 99%